Masonry compression : a numerical investigation at the meso-level - Henriques, J. Pina (2006)
The analysis of masonry assemblages under compression using detailed modelling strategies in which units and mortar are modelled separately is a challenging task. Sophisticated standard non-linear continuum models, based on plasticity and cracking, are widely available to represent the masonry components but such models overestimate the experimental strength of masonry prisms under compression. Alternative modelling approaches are therefore needed. This paper focuses on the discussion and detailed analysis of a particle model consisting in a phenomenological discontinuum approach to represent the micro-structure of units and mortar. The micro-structure attributed to the masonry components is composed by linear elastic particles of polygonal shape separated by non-linear interface elements. All the inelastic phenomena occur in the interfaces and the process of fracturing consists of progressive bond-breakage. Clear advantages have been shown by the particle model, when compared to standard continuum models.